The Role of Teachers' Job Engagement and Job Satisfaction in Prediction Students' School Bonding - Ali Sheykholreslami; Robab Dadjooei; Nastaran Seyedesmaili Ghomi (مطالعات روانشناسی تربیتی, 2020)
The purpose of this study was to investigate the role of teachers' job engagement and job satisfaction in prediction students' school bonding. This research was applied in terms of purpose and correlational in terms of descriptive method. The statistical population of this study consisted of all female high school students in the second district of Ardabil and also teachers in this district in the 2015-2016 academic year, among whom using random sampling method. Clustering, 720 people (144 teachers and 576 students) were selected as the sample. For data collection, Cernkovich, and Giordano School Bonding Questionnaire, Schaufeli and Bakker Job Engagement Questionnaire and MSQ Job Satisfaction Questionnaire were used. Data were analyzed by using Pearson’s correlation coefficient and regression analysis. Findings showed that there is a significant positive relationship between job satisfaction and job satisfaction of teachers with the connection with students' school (p < 0.01). Also, the results of regression analysis showed that teachers 'job motivation and job satisfaction predict approximately 23% of the variance related to students' connection with school (p < 0.01). As a result, it can be said that teachers' job engagement and job satisfaction have the ability to predict the students' school bonding and require programs to improve these variables in teachers.